AN OVERVIEW OF BREASTFEEDING SELF-EFFICACY AMONG THIRD-TRIMESTER PREGNANT WOMEN - Diva Loliza; Linda Yulyani; Novianti; Yetti Purnama; Asmariyah (Poltekkes Kemenkes Banten, 2026)
Low exclusive breastfeeding (EBF) coverage is a contributing factor to the relatively high Infant Mortality Rate in Indonesia. In 2023, global EBF coverage was 48%, whereas Indonesia's coverage declined from 67.98% in 2022 to 63.9% in 2023. This study aimed to provide an overview of EBF self-efficacy among third-trimester pregnant women.. A survey was conducted using the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF) questionnaire with a quota sample of 60 pregnant women in the working area of the Kandang Health Center, Bengkulu City. The results showed that the majority of respondents were aged 20-35 years (86.7%), high school graduates (51.7%), and employed (58.3%), with over half being multiparous (55%). Based on the BSES-SF results, only 50% of the respondents demonstrated a good level of self-efficacy, while 41.7% had a moderate level and 8.3% a low level. The study concludes that only half of the pregnant women in this population possess a good level of breastfeeding self-efficacy, indicating that the remainder require further support, communication, information, and education from healthcare providers to improve their breastfeeding self-efficacy.